2021
DOI: 10.3389/fgene.2021.641100
|View full text |Cite
|
Sign up to set email alerts
|

Unearthing of Key Genes Driving the Pathogenesis of Alzheimer’s Disease via Bioinformatics

Abstract: Alzheimer’s disease (AD) is a neurodegenerative disease with unelucidated molecular pathogenesis. Herein, we aimed to identify potential hub genes governing the pathogenesis of AD. The AD datasets of GSE118553 and GSE131617 were collected from the NCBI GEO database. The weighted gene coexpression network analysis (WGCNA), differential gene expression analysis, and functional enrichment analysis were performed to reveal the hub genes and verify their role in AD. Hub genes were validated by machine learning algo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…While the overlaps between ASD and conditions such as ADHD, obsessive-compulsive disorder (OCD), intellectual disability (ID), and epilepsy have been well-established (Viscidi et al, 2013; Kushki et al, 2019; Thurm et al, 2019), potential links between ASD and other disorders are less clear. Interestingly, several of our novel ASD-associated genes have tentative links with neurodegenerative disorders, such as Alzheimer’s disease (AD)— NR4A 2 (Jesús et al, 2021; Moon et al, 2019), ATP2B2 (Brendel et al, 2014), EIF4E (Li et al, 2004; Ghosh et al, 2020), EBF3 (Rao et al, 2018), MARK2 (Segu et al, 2008; Gu et al, 2013; Zhou et al, 2019), EPOR (Brettschneider et al, 2006; Hernández et al, 2017), G3BP1 (Martin et al, 2013; Silva et al, 2019), PLXNB1 (Yu et al, 2018; Zhao et al, 2021), APBB1 (McLoughlin and Miller, 2008; Zeidán-Chuliá et al, 2014; Probst et al, 2020), and ANP32A (Chai et al, 2017, 2018; Podvin et al, 2020). The link between ASD and neurodegenerative disease may also extend to X-linked genes; for example, variants in RAB39B have been linked to both (Mata et al, 2015; Woodbury-Smith et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…While the overlaps between ASD and conditions such as ADHD, obsessive-compulsive disorder (OCD), intellectual disability (ID), and epilepsy have been well-established (Viscidi et al, 2013; Kushki et al, 2019; Thurm et al, 2019), potential links between ASD and other disorders are less clear. Interestingly, several of our novel ASD-associated genes have tentative links with neurodegenerative disorders, such as Alzheimer’s disease (AD)— NR4A 2 (Jesús et al, 2021; Moon et al, 2019), ATP2B2 (Brendel et al, 2014), EIF4E (Li et al, 2004; Ghosh et al, 2020), EBF3 (Rao et al, 2018), MARK2 (Segu et al, 2008; Gu et al, 2013; Zhou et al, 2019), EPOR (Brettschneider et al, 2006; Hernández et al, 2017), G3BP1 (Martin et al, 2013; Silva et al, 2019), PLXNB1 (Yu et al, 2018; Zhao et al, 2021), APBB1 (McLoughlin and Miller, 2008; Zeidán-Chuliá et al, 2014; Probst et al, 2020), and ANP32A (Chai et al, 2017, 2018; Podvin et al, 2020). The link between ASD and neurodegenerative disease may also extend to X-linked genes; for example, variants in RAB39B have been linked to both (Mata et al, 2015; Woodbury-Smith et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has been recently evidenced that MAOB levels were higher in the frontal cortex, hippocampus CA1 and entorhinal cortex of AD brain than in controls, that the enzyme is a γ-secretase-associated protein and that intraneuronal Aβ 42 levels correlated with MAOB levels [62]. Importantly, this molecular and genetic evidence has recently been reinforced by bioinformatics studies using microarray datasets that have detected higher expression of MAOA, MAOB and COMT in the brain of AD patients when compared to control individuals [63-65] and modified COMT expression in the hippocampus of AD patients [66]. Furthermore, a meta analytic review has also reported a significant increase in hippocampal MAOB expression in AD [67].…”
Section: Discussionmentioning
confidence: 99%
“…PTPRZ1 SNPs significantly associating with the risk to develop schizophrenia have been reported ( Buxbaum et al, 2008 ) but the gene’s link with Alzheimer’s Disease thus far is based on expression levels of RPTPζ isoforms and of its ligand pleiotrophin in postmortem material ( Zhao et al, 2021 ). Because schizophrenia-associated genes represent promising candidates for predicting antidepressant efficacy, Su and others have tested five PTPRZ1 SNPs for an association with anxiety remission status in two Chinese cohorts that were stratified for the medication received, but correction for multiple testing aborted the potential associations ( Su et al, 2021a ).…”
Section: Documented Genetic Variabilitymentioning
confidence: 99%